Project management, planning and control managing engineering, construction and manufacturing projects to PMI, APM and BSI standards - Lester, Albert; Lester, Albert (Amsterdam ; Boston ; London : Elsevier/Butterworth-Heinemann, 2007)
Fully aligned with the latest 2006 Project Management Body of Knowledge (PMBOK) for both the Project Management Institute (PMI) and the Association of Project Management (APM), this book is a vital study aid for any Project Management Professional (PMP) qualification and reference that practising project managers will want to keep to hand. Each of the core project management topics and principles is explained and applied through a careful balance of theory and practical examples. With its real-life case studies of engineering, manufacturing and construction projects, clear summaries and self-test resources, the book is a complete guide for any project manager. The author: Albert Lester was a project manager with Tarmac Construction and Foster Wheeler Power Products, managing large multi-discipline projects. He has been a compiler and examiner for the APMP certificate, lectures on project management and has assessed many project management courses for APM. * Covers the complete body of knowledge for project management professionals in the engineering, manufacturing & construction sectors * Covers all theory & practice for the newly revised PMI and APM qualification exams and the latest version of BS 6079-1:2002 * Online Q & A resources for self-testing written by a qualified PMP exam accreditor.
Project definition; Project management; Program management; Project environment; Business case; Investment appraisal, DCF, NPV; Stakeholder analysis; Project success criteria; Organization structures; Organizational roles; Project life cycle; Work content & scope (WBS); Planning blocks & subdivision of blocks; Estimating; Project management plan; Risk management; Quality management; Change management; Configuration management; Time management, Basic network principles; Analysis types; Precedence diagrams; Lester diagram; Float; Milestones & line of balance; Simple examples; Progress reporting; Project management and planning; Network applications outside the construction industry; Resource management, Histograms, S Curves; Cash flow and cash flow curves; Budgeting, cost control & earned value analysis; Control graphs and reports; Procurement; Value management & value engineering; Health & safety & environment; Information management; Communication; Teamwork; Leadership; Negotiation; Conflict management & dispute resolution; Project close-out and hand over; Project close-out report and review; Worked example 1: Small bungalow; Worked example 2: Pumping installation; Worked example 3: Motor car; Worked example 4: Battle tank; Hornet Windmill program; Stages and sequences; Abbreviations & acronyms; Glossary; APMP learning objectives; Typical question areas; Summary of essential features; Bibliography; Index.
Previous ed.: published as Project planning and control. Oxford: Elsevier Butterworth-Heinemann, 2003.
Includes bibliographical references (p. [422]-426) and index.
Keywords: Project management; Process control; Project Management -- Data processing; Electronic books